The human brain in ancient Egypt : a medical and historical re-evaluation of its function and importance - Aziz, Sofia, (Archaeopress Egyptology ;, 2023)
This text provides a medical and historical re-evaluation of the function and importance of the human brain in ancient Egypt. The study evaluates whether treatment of the brain during anthropogenic mummification was linked to medical concepts of the brain.